Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So there is a linear system

$ \frac{du}{dt} = - \left( \begin{array}{cc} 4 & -3 \\ 6 & -5 \end{array} \right) \frac{du}{dx} $

with an initial condition

$ u(x, 0)= \left( \begin{array}{c} -tanh(\lambda x) \\ 0 \end{array} \right) $

Now to start this off I have manipulated the first equation to get this

$ \left( \begin{array}{ccc} 1 & \frac{-3}{4} & -\frac{1}{4} \frac{du_{1}}{dt}\\ 0 & \frac{1}{12} & \frac{1}{6} \frac{du_{2}}{dt}-\frac{1}{4} \frac{du_{1}}{dt}\end{array} \right) \frac{du}{dx} $

which can be rewritten as

$ \left( \begin{array}{ccc} 1 & \frac{-3}{4} & -\frac{1}{4} \frac{du_{1}}{dt}\\ 0 & \frac{1}{12} & \frac{1}{6} \frac{du_{2}}{dt}-\frac{1}{4} \frac{du_{1}}{dt}\end{array} \right) \frac{du}{dx} =>\left( \begin{array}{cc} 1 & \frac{-3}{4}\\ 0 & \frac{1}{12}\end{array} \right) \frac{du}{dx} = \left( \begin{array}{c} -\frac{1}{4} \frac{du_{1}}{dt} \\ \frac{1}{6} \frac{du_{2}}{dt}-\frac{1}{4} \frac{du_{1}}{dt} \end{array} \right) $

but I'm not sure how to deal with the derivatives. Would I use what I already have but just plug in the initial condition to $u_{1}$ and $u_{2}$ or am I using the wrong method?

share|improve this question
    
I added the tag "differential equations", I think it is more than appropriate here than just "linear-algebra". –  Patrick Da Silva Mar 27 '12 at 0:26

1 Answer 1

up vote 1 down vote accepted

If one writes $u=(u_1,u_2)$ and one diagonalizes the matrix $A$, one gets the simpler differential system $\frac{\partial v_1}{\partial t}=-\frac{\partial v_1}{\partial x}$ and $\frac{\partial v_2}{\partial t}=2\frac{\partial v_2}{\partial x}$, with $v_1=u_1+u_2$ and $v_2=u_1+2u_2$.

For any $a$, the differential equation $\frac{\partial v}{\partial t}=a\frac{\partial v}{\partial x}$ means that $v$ is a function of $x+at$, hence that $v(x,t)=v(x+at,0)$. Here, $v_1(x,t)=v_1(x-t,0)$ and $v_2(x,t)=v_2(x+2t,0)$.

Finally, $u_1=2v_1-v_2$ and $u_2=v_2-v_1$ hence $$ u_1(x,t)=2u_1(x-t,0)+2u_2(x-t,0)-u_1(x+2t,0)-2u_2(x+2t,0), $$ and $$ u_2(x,t)=-u_1(x-t,0)-u_2(x-t,0)+u_1(x+2t,0)+2u_2(x+2t,0). $$ In the special case when $u_1(x,0)=u_0(x)$ and $u_2(x,0)=0$, one gets $$ u_1(x,t)=2u_0(x-t)-u_0(x+2t),\quad u_2(x,t)=u_0(x+2t)-u_0(x-t). $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.